Effects of ultrasound-assisted enzymolysis on extraction of beta-glucan enriched lysates and cell wall of Saccharomyces cerevisiae - Ismail, Azimah Shaik; Abbasiliasi, Sahar; Sreedharan, Dharni Kuhan; Lee, Chee Keong; Muthulakshmi, Lakshmanan; Tan, Joo Shun (Springer, 2024)
Saccharomyces cerevisiae is being used for long as a rich source of proteins, sugars, nucleotides, vitamins, and minerals. Yeast lysates from autolyzed and hydrolyzed yeast cells have found numerous applications in the food industry. This study explored the feasibility of producing yeast lysates using an enzymolysis approach and proposed an ultrasonic-assisted enzymolysis process to realize yeast extract production with high total soluble solids. The efficiency of each process was compared and evaluated based on total soluble solids (Brix), protein content (mg/mL), cell viability (log CFU/mL), dry weight of yeast extract (mg/mL), and dry weight of cell wall (mg/mL). Results indicated that the total soluble solids and dry weight of yeast extract were higher using ultrasonic-assisted enzymolysis compared to those of autolysis and enzymolysis treatments. The ultrasonic-assisted enzymolysis parameters consisted of 0.1 Alcalase with 50 power, 80 pulse after 30 min, completely attenuated S. cerevisiae cells, and yielded the highest yeast extract and cell wall. A total of 9.62 ( w/w) of beta-glucan in the yeast extract was obtained through this process. This study for the first time explored the feasibility of utilizing the peptidase with the assistance of ultrasonication to produce Baker’s yeast extract and use it as a food supplement. In addition, the cell wall from the lysis treatment can be used as an agent for microencapsulating probiotics. © 2024, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.